Use of buccal fat pad flap for premalignant buccal mucosa defect reconstruction - Kshirsagar, Pankaj; Nichkaode, Prabhat B.; Reddy, Saicharan; Chamakura, Manichandra (International Surgery Journal, 2020)
Premalignant lesions over buccal mucosa are very common in India, some of these lesions require excision leaving behind defects and various techniques can be used in reconstruction of these defects. Small palatal defect, oroantral fistulas have been successfully closed by buccal pad of fat flap. Aim of this study was to evaluate reconstruction of defects after excision of premalignant lesion over buccal mucosa using buccal pad of fat. 20 patients were selected for this study who presented with different premalignant lesions like erythroplakia, proliferative verrucous leukoplakia, chronic hyperplastic candidiasis, Oral submucous fibrosis over buccal mucosa in Dr. DY Patil medical college surgery unit 4 and 7. Excision of lesion followed by reconstruction with buccal pad of fat was done. Patients were followed up every 14 days for 14 weeks, and was evaluated for epithelisation of flap and post-operative complications like infection and flap necrosis and also the functionality of the flap. In this study we have observed complete epithelisation of the flap in most of our patients. Dehiscence of the wound was observed in 3 of the patients with large defects (>4×5 cm). No postoperative morbidity was in postoperative patients. Buccal pad of fat is an excellent technique for reconstruction of small defects of buccal mucosa. It is a reliable and a fast method which has easy accessibility less complications and minimal morbidity.